Spirituality as Process: Four Dimensions of Following Christ in The Imitation of Christ - Pansters, Krijn (2023)
The Imitation of Christ of Thomas a Kempis (†1471) is a true classic of Christian spirituality. The devotional work consists of four books: ‘Counsels Helpful for the Spiritual Life’, ‘Counsels Concerning the Interior Life’, ‘Inward Exhortation to Holy Communion’, and ‘Book On Inner Consolation’. This article offers a spiritual analysis of the 25 chapters of the first book for the purpose of the modern use of this medieval bestseller in the context of personal and professional growth. It focuses not on static theological statements but on aspects of the spiritual process of advancing on the way to Christ. More specifically, it looks at four distinguished dimensions of following Christ: devotion (devotio), virtue (virtus), desire (desiderium), and dedication (diligentia, etc.). The purpose is threefold. First, these four inward dimensions suggest four interrelated ways of going forward, progressing, and growing spiritually. Second, they demonstrate a dynamic approach not only to spiritual fulfilment but also to spiritual texts. Third, they direct our attention to spirituality as a progressive, ongoing process.